Audit Quality Attributes Of European Supreme Audit Institutions: An Examination Of Independence And Accountability Provisions - Krambia-Kapardis, Maria; Clark, Colin; Martinis, Michael De (My University, 2003)
To examine the enabling legislation of European Union (EU) member country supreme audit institutions (SAIs) for their accountability to parliament and independence from the executive arm of government.